2016
DOI: 10.1371/journal.pone.0152602
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arch Compression and Metatarsophalangeal Joint Dynamics in Modulating Plantar Fascia Strain in Running

Abstract: Elastic energy returned from passive-elastic structures of the lower limb is fundamental in lowering the mechanical demand on muscles during running. The purpose of this study was to investigate the two length-modulating mechanisms of the plantar fascia, namely medial longitudinal arch compression and metatarsophalangeal joint (MPJ) excursion, and to determine how these mechanisms modulate strain, and thus elastic energy storage/return of the plantar fascia during running. Eighteen runners (9 forefoot and 9 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 42 publications
12
111
0
3
Order By: Relevance
“…Recently, McDonald et al (2016) and Wager and Challis (2016) used 3-D musculoskeletal modeling to argue that the plantar aponeurosis is a major site of elastic energy storage during running. Furthermore, Kelly et al (2015) found evidence that the intrinsic foot muscles also stretch actively to absorb energy in the first half of stance during running, potentially storing energy that could be released when they shorten in the second half of stance.…”
Section: Elastic Energy Storage and Releasementioning
confidence: 99%
“…Recently, McDonald et al (2016) and Wager and Challis (2016) used 3-D musculoskeletal modeling to argue that the plantar aponeurosis is a major site of elastic energy storage during running. Furthermore, Kelly et al (2015) found evidence that the intrinsic foot muscles also stretch actively to absorb energy in the first half of stance during running, potentially storing energy that could be released when they shorten in the second half of stance.…”
Section: Elastic Energy Storage and Releasementioning
confidence: 99%
“…For example, muscle hypertrophy in the foot may induce modifications of foot arch height, which may help store the elastic energy absorbed by the MTP joint during the stance phase of sprinting, and subsequently enhance the plantar flexor moment via increasing MTP joint moment using the returned energy during push-off phase. 6,7,22 Thus, further studies are needed to examine the relationships among the length of the forefoot bones, size of the foot muscles, and foot proportions such as foot arch height. Finally, we determined that, in sprinters, the forefoot bone length is related to sprint performance, with faster sprinters having longer forefoot bones than slower sprinters.…”
Section: T a B L E 2 Physical Characteristics Andmentioning
confidence: 99%
“…[1][2][3] Moreover, it has been proposed that the elastic energy returned in the form of the MTP joint moment can partially utilize the enhancement of plantar flexor moment during push-off phase. [4][5][6][7][8] Thus, while the MTP joint is a relatively small joint, its moment during sprinting may be related to superior sprint performance.…”
Section: Introductionmentioning
confidence: 99%
“…The developed intrinsic foot muscles may cause the increase of foot arch height, and the increased foot arch height may be useful to create the foot with long forefoot bones. Additionally, previous studies determined that the absorbed energy in the MTP joint during running may be stored within the plantar aponeurosis, and this energy may be utilized as elastic energy [12,26]. The increase of the external MTP joint moment related to longer forefoot bones may result from development of the plantar aponeurosis because of increased eccentric and concentric moments.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, larger ankle plantar flexor moments play an important role in achieving higher running performance compared to other lower limb joint moments [9,15]. The metatarsophalangeal (MTP) flexor moment in the foot contributes to enhancing the plantar flexor moment [1,10], potentially by storing and then returning the elastic energy during human locomotion, including running [2,8,12,21,26]. Thus, despite being a relatively small joint, the MTP joint moments may play a significant role in superior running performance.…”
Section: Introductionmentioning
confidence: 99%